Thromboembolic safety profile of low-dose estradiol (valerate) in combined hormonal preparations: Implications for the development of new hormonal endometriosis and uterine fibroid therapies. Issue 3 (September 2021) - Barnett, Clare; Bauerfeind, Anja; von Stockum, Sophia; Heinemann, Klaas
Background: Several promising new medications containing low-dose estradiol (E2) in combination with a progestin and an additional component, such as gonadotropin-releasing hormone antagonists, are currently being developed for use in pre-menopausal women. Objective: This pooled analysis was designed to estimate the thromboembolic safety profile of E2 and its ester, estradiol valerate (E2Val), when used in combined hormonal treatments in a pre-menopausal population. Methods: Data regarding users of combined oral contraceptives (COCs) and combined menopausal hormonal therapy (MHT) containing either E2/E2Val or ethinylestradiol (EE) ⩽ 30 µg were retrieved from five large prospective, non-interventional, cohort studies in Europe, US, and Canada with similar study design but differing medication cohorts. Propensity score sub-classification was applied to balance baseline parameters between cohorts and time-to-event analysis of venous thromboembolic events (VTE) was carried out based on the extended Cox model to calculate crude and adjusted hazard ratios (HR). Results: (1) Crude incidence rates of VTE were higher in MHT users compared to pre-menopausal COC users, (2) the VTE risk in menopausal users of E2/E2Val-norethindrone acetate was not higher than that in menopausal users of E2/E2Val-progestin (adjusted HR 0.71; 95% confidence interval, 0.41-1.26) and (3) the VTE risk in pre-menopausal users of E2/E2Val-progestin was similar, or lower, than pre-menopausal users of EE⩽30µg-progestin (adjusted HR 0.49; 95% confidence interval, 0.28–0.84). Conclusion: Our data presents a solid safety assessment of combined hormonal preparations containing E2/E2Val. We conclude that the risk of E2/E2Val-norethindrone acetate in pre-menopausal users is unlikely to be higher than the known risk of COCs containing EE ⩽ 30 µg-progestin.